The importance of school leaders in school health promotion. A European call for systematic integration of health in professional development - Leksy, Karina; Gawron, Grzegorz; Rosário, Rafaela; Sormunen, Marjorita; Velasco, Veronica; Sandmeier, Anita; Simovska, Venka; Wojtasik, Tomasz; Dadaczynski, Kevin (Frontiers in Public Health, 2024)
School leaders such as principals are key not only for educational and school quality but also for initiating and sustainably anchoring any innovation in schools. Although there is widespread agreement about the importance of holistic approaches to school health promotion, the role of principals has received increased, but not yet systematic, attention. In this context, it is unclear which leadership competencies are needed and to what extent they are taught. Hence, this paper aims to reflect whether and to what extend health promotion plays a role in preservice and inservice training of principals in Europe. Based on the results we call for a more systematic analysis of existing teaching opportunities and teaching needs for health-promoting leadership, the development of a European competence framework for health-promoting leadership, the development and implementation of a European system that monitors and evaluates the effectiveness of those preservice and inservice training programs, and the development of case-studies to stimulate a mutual learning process.